Transcriptomic profiling of microbe–microbe interactions reveals the specific response of the biocontrol strain P. fluorescens In5 to the phytopathogen Rhizoctonia solani - Rosanna C. Hennessy; Mikkel A. Glaring; Stefan Olsson; Peter Stougaard (BMC Research Notes, 2017)
Abstract Background Few studies to date report the transcriptional response of biocontrol bacteria toward phytopathogens. In order to gain insights into the potential mechanism underlying the antagonism of the antimicrobial producing strain P. fluorescens In5 against the phytopathogens Rhizoctonia solani and Pythium aphanidermatum, global RNA sequencing was performed. Methods Differential gene expression profiling of P. fluorescens In5 in response to either R. solani or P. aphanidermatum was investigated using transcriptome sequencing (RNA-seq). Total RNA was isolated from single bacterial cultures of P. fluorescens In5 or bacterial cultures in dual-culture for 48 h with each pathogen in biological triplicates. RNA-seq libraries were constructed following a default Illumina stranded RNA protocol including rRNA depletion and were sequenced 2 × 100 bases on Illumina HiSeq generating approximately 10 million reads per sample. Results No significant changes in global gene expression were recorded during dual-culture of P. fluorescens In5 with any of the two pathogens but rather each pathogen appeared to induce expression of a specific set of genes. A particularly strong transcriptional response to R. solani was observed and notably several genes possibly associated with secondary metabolite detoxification and metabolism were highly upregulated in response to the fungus. A total of 23 genes were significantly upregulated and seven genes were significantly downregulated with at least respectively a threefold change in expression level in response to R. solani compared to the no fungus control. In contrast, only one gene was significantly upregulated over threefold and three transcripts were significantly downregulated over threefold in response to P. aphanidermatum. Genes known to be involved in synthesis of secondary metabolites, e.g. non-ribosomal synthetases and hydrogen cyanide were not differentially expressed at the time points studied. Conclusion This study demonstrates that genes possibly involved in metabolite detoxification are highly upregulated in P. fluorescens In5 when co-cultured with plant pathogens and in particular the fungus R. solani. This highlights the importance of studying microbe–microbe interactions to gain a better understanding of how different systems function in vitro and ultimately in natural systems where biocontrol agents can be used for the sustainable management of plant diseases.